Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To calculate the average rate of change of the function [tex]\( f(x) = x^2 + 5x - 12 \)[/tex] from [tex]\( x = -2 \)[/tex] to [tex]\( x = 1 \)[/tex], let's go through the steps:
1. First, we find the values of the function at [tex]\( x = -2 \)[/tex] and [tex]\( x = 1 \)[/tex].
- Evaluating the function at [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = (-2)^2 + 5(-2) - 12 = 4 - 10 - 12 = -18 \][/tex]
Therefore, [tex]\( f(-2) = -18 \)[/tex].
- Evaluating the function at [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 1^2 + 5(1) - 12 = 1 + 5 - 12 = -6 \][/tex]
Therefore, [tex]\( f(1) = -6 \)[/tex].
2. Next, we calculate the change in [tex]\( y \)[/tex] (i.e., the difference between the function values at these points):
[tex]\[ \Delta y = f(1) - f(-2) = -6 - (-18) = -6 + 18 = 12 \][/tex]
3. The change in [tex]\( x \)[/tex] is given by the difference in the [tex]\( x \)[/tex]-values. Here, [tex]\( x \)[/tex] changes from [tex]\( -2 \)[/tex] to [tex]\( 1 \)[/tex]:
[tex]\[ \Delta x = 1 - (-2) = 1 + 2 = 3 \][/tex]
4. Finally, we find the average rate of change by dividing the change in [tex]\( y \)[/tex] by the change in [tex]\( x \)[/tex]:
[tex]\[ \text{Average rate of change} = \frac{\Delta y}{\Delta x} = \frac{12}{3} = 4 \][/tex]
Summarizing the steps:
- [tex]\( f(-2) = -18 \)[/tex]
- [tex]\( f(1) = -6 \)[/tex]
- Change in [tex]\( y = 12 \)[/tex]
- Change in [tex]\( x = 3 \)[/tex]
- Average rate of change = 4
Therefore, the average rate of change of the function [tex]\( f(x) \)[/tex] from [tex]\( x = -2 \)[/tex] to [tex]\( x = 1 \)[/tex] is [tex]\( 4 \)[/tex].
1. First, we find the values of the function at [tex]\( x = -2 \)[/tex] and [tex]\( x = 1 \)[/tex].
- Evaluating the function at [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = (-2)^2 + 5(-2) - 12 = 4 - 10 - 12 = -18 \][/tex]
Therefore, [tex]\( f(-2) = -18 \)[/tex].
- Evaluating the function at [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 1^2 + 5(1) - 12 = 1 + 5 - 12 = -6 \][/tex]
Therefore, [tex]\( f(1) = -6 \)[/tex].
2. Next, we calculate the change in [tex]\( y \)[/tex] (i.e., the difference between the function values at these points):
[tex]\[ \Delta y = f(1) - f(-2) = -6 - (-18) = -6 + 18 = 12 \][/tex]
3. The change in [tex]\( x \)[/tex] is given by the difference in the [tex]\( x \)[/tex]-values. Here, [tex]\( x \)[/tex] changes from [tex]\( -2 \)[/tex] to [tex]\( 1 \)[/tex]:
[tex]\[ \Delta x = 1 - (-2) = 1 + 2 = 3 \][/tex]
4. Finally, we find the average rate of change by dividing the change in [tex]\( y \)[/tex] by the change in [tex]\( x \)[/tex]:
[tex]\[ \text{Average rate of change} = \frac{\Delta y}{\Delta x} = \frac{12}{3} = 4 \][/tex]
Summarizing the steps:
- [tex]\( f(-2) = -18 \)[/tex]
- [tex]\( f(1) = -6 \)[/tex]
- Change in [tex]\( y = 12 \)[/tex]
- Change in [tex]\( x = 3 \)[/tex]
- Average rate of change = 4
Therefore, the average rate of change of the function [tex]\( f(x) \)[/tex] from [tex]\( x = -2 \)[/tex] to [tex]\( x = 1 \)[/tex] is [tex]\( 4 \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.